The Shackles of Identity: The “Chevalier Saint-Georges” as a Flawed Romantic Hero - Frigerio, Vittorio (Alternative francophone)

(untitled) (University of Alberta, Department of Modern Languages and Cultural Studies, 2025)
This article discusses the presumed relationship between the Chevalier de Saint-Georges and the novelist Alexandre Dumas, and analyzes a novel by one of Dumas’ friends, Roger de Beauvoir, allegedly based on the Chevalier’s life. This novel uses melodramatic tropes to propose a comment on the decadence of the French monarchy, as symbolically mirrored by the mulatto’s rise in Parisian society, as well as on matters of social and racial identity.